The orthopaedic management of long bone deformities in genetically and acquired generalized bone weakening conditions. (1st February 2019) - Wirth, T.
Abstract: Purpose: Diseases such as osteogenesis imperfecta, fibrous dysplasia, hypophosphataemic rickets and others lead to soft and weak bones and long bone deformity in affected patients. As a consequence, these patients lose their walking capacity and functional abilities of the upper extremities as well. Methods: In combination with bisphosphonate treatment and physical rehabilitation programmes surgical interventions are being applied to correct and stabilize the deformed and less mechanically resistant long bones. Intramedullary devices, ideally with an elongating telescopic mechanism, have proven to be the most suitable implants. Results: The surgical correction and stabilization of deformed bones in weak bone diseases is very beneficial to the patients. Pain restriction, reduction of fracture events, minimization of consequences of traumatic events and falls have resulted in a significant functional improvement. The patients live on a better activity level with a much-improved individual independence. Despite a high complication and revision rate of the intramedullary rods the gain of quality of life outweighs these negative aspects by far. Conclusion: Orthopaedic surgical treatment for deformed bones in patients with weak bone diseases has changed the life of the patients and plays a very important role in the disease management protocols. This paper was written under the guidance of the Study Group Genetics and Metabolic Diseases of the European Paediatric Orthopaedic Society.